Historia e rigor na iniciaçao ao cálculo: uma experiencia cubana - Valdés Castro, Concepción; Sánchez Fernández, Carlos (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2011)
O objetivo principal deste artigo foi compartilhar nossas experiências no desenvolvimento de um curso introdutor do Cálculo usando problemas históricos. Nesse enfoque se pretende apresentar aos estudantes não somente os obstáculos achados na resolução de significativos problemas históricos, mas também as idéias e métodos usados na sua superação. Realmente pretendemos argumentar que uma adequada reconstrução do contexto histórico desses proveitosos problemas pode incrementar a motivação do estudante e facilitar uma assimilação mais razoável da necessária metodologia ε-δ nos cursos avançados da Análise Matemático. Abstract The main goal of this paper is to share our experiences in the development of an introductory Calculus course through the use of historical problems. With this approach we present to the students both the obstacles encountered in the resolution of meaningful historical problems and the ideas and methods by which theses obstacles have been overcome. In fact we would argue that a suitable reconstruction of the historical context of these fruitful problems can be valuable to improve the student motivation and to move more reasonably towards the indispensable ε-δ methodology in advanced courses of Mathematical Analysis. Keywords: Integration of history in the teaching of Calculus; introduction to Calculus; transit to the college education.